The free trade area of the Asia-Pacific: A constructive approach to multilateralizing Asian regionalism - C. Fred Bergsten; Marcus Noland; Jeffrey J. Schott (Asian Development Bank Institute (ADBI), 2011)
This paper examines the prospect of realizing regional economic integration via the mechanism of a Free Trade Area of the Asia-Pacific (FTAAP). The FTAAP initiative represents a politically ambitious, high potential benefit option for achieving Asian regional integration. Among its desirable attributes, the FTAAP initiative could help revive and promote a successful conclusion of the Doha Round negotiations; constitute a "Plan B" hedge if Doha fails; short-circuit the further proliferation of bilateral and sub-regional preferential agreements that create substantial new discrimination and discord within the Asia-Pacific region; defuse the renewed risk of "drawing a line down the middle of the Pacific" as East Asian, and perhaps the Western Hemisphere, initiatives produce disintegration of the Asia-Pacific region rather than the integration of that broader region that the Asia-Pacific Economic Cooperation (APEC) forum was created to foster; channel the People's Republic of China-United States economic conflict into a more constructive and less confrontational context; and revitalize APEC, which is of enhanced importance because of the prospects for Asia-Pacific and especially the PRC-US fissures. An incremental approach to the FTAAP, explicitly embodying enforceable reciprocal commitments, offers the best hope delivering on the concept's abundant benefits.
Keywords: O16; O53; R11; 330; regional economic integration; asia-pacific; doha round negotiations; Freihandelszone; Regionale Wirtschaftsintegration; Asiatisch-pazifischer Raum